Asymmetry Factor application based on the sectorization of watersheds: Morphostructural analysis of the Chopim River catchment, Paraná State (Brazil) - Peyerl, William Rudolf Lopes; Salamuni, Eduardo (Revista Brasileira de Geomorfologia, 2024)
The watershed asymmetry factor is a morphometric index used to search structural influence in the landscape. However, this toll is subjected to the camouflage effect, when some features could be omitted because of its size, age or dissection’s state. The watershed sectorization was developed to introduce a new concept that refine the applying the asymmetry factor. Compartmentalize the catchment in sectors using geological and/or geomorphic patterns contributes to the structural impact of relief becoming better dimensioned, in the same way allowing the compartmentation of any data analyzed in the watershed. The Chopim River (southern Paraná) lies between some important fault zones and have none lithological abrupt variation or relevant climatic changes, thereat it was selected to apply the new method. The watershed sectorization was fundamental to recognize the influence of Taxaquara fault in the Chopim catchment threw light in the relation in Taxaquara and other fault zones in the watershed development.